The variation of riverine heavy metal flux using RUSLE model in the Ranau sub‑basins, Malaysia. Adjacent to ultrabasic soil - Muhammad Rendana; Wan Mohd Razi Idris; Sahibin Abdul Rahim (Kluwer Academic Publishers, 2022)
The ultrabasic soils exhibit sources of natural geogenic contamination and potential to contaminate soil and water resources. In Ranau basin area, Malaysia, there are three sub-basins which locate adjacent to the ultrabasic soil. The transport of metals concentration can be assessed using the riverine heavy metal flux analysis based on the empirical erosion models. The erosion models such as the Revised Universal Soil Loss Equation (RUSLE) give a common and extensive framework for evaluating soil erosion and its causative factors. RUSLE examined rainfall (R), topography (LS), soil erodibility (K), cover management (C), and support practice (P) as prominent factors influencing soil erosion. Several heavy metals (Co, Cr, Ni, Pb, Cu, and Zn) and a toxic element (As) were analyzed in this study using the standard laboratory analysis. Results of study revealed the average of soil erosion rates in the sub-basins was higher than the national standard of soil erosion rate were 215.10 ton/ha year (very high class, > 150 ton/ha year), 113.29 ton/ha year (high class, 100–150 ton/ha year), and 67.53 ton/ha year (moderate high class, 50–100 ton/ha year) in the Langanan, Liwagu, and Lohan respectively. The riverine heavy metal flux was the highest for Ni, Cu, Pb, and Zn in the Langanan (1.51 kg/ha year, 2.77 kg/ha year, 6.71 kg/ha year, and 118.95 kg/ha year, respectively). The heavy metal flux was highest for Cr and Co in the Liwagu (311.57 kg/ha year and 10.91 kg/ha year). The concentration of heavy metals in rice grains in descending order was Cr > Ni > Zn > Cu > Pb > Co. The biological absorption coefficient (BAC) values for all of the heavy metals were below 0.12 which indicated that rice plants in the study area did not accumulate heavy metals. These results have a prominent notion to discover the distribution and transport of heavy metals in the sub-basins to arrange the best solution in controlling of source heavy metal pollution due to ultrabasic soil.